AN ANALYSIS ON THE COMPATIBILITY OF REAL COST AND INA-CBGS COST DETERMINATION IN RECTUM CANCER CHEMOTHERAPY PATIENT TO THE IMPLEMENTATION OF NATIONAL HEALTH INSURANCE IN SANGLAH CENTRAL GENERAL HOSPITAL OF DENPASAR IN 2014 - Lelie Amalia Tusshaleha (Jurnal Ilmiah Mandala Education (JIME), 2018)
The problem frequently found in JKN (National Health Insurance) implementation the payment of which is based on INA-CBGs tariff is the difference of real cost and the INA-CBGs tariff. The objective of research was to find out the difference of real cost without chemotherapy and INA-CBGs tariff, the highest cost component in real cost without chemotherapy, and to find out the amount of real cost without chemotherapy related to the chemotherapy cycle regularity in rectum cancer inpatient in Sanglah Central General Hospital of Denpasar (RSUP Sanglah Denpasar). This study was an observational research with cross sectional design according to the hospitals’ perspective. The data was collected retrospectively including the document of claim and treatment cost for rectum cancer chemotherapy patient in January-August 2014. The data was analyzed using one sample t-test to compare the real cost and the INA-CBGs tariff. The result of research showed the positive average difference of cost real from INA-CBGs tariff in which in C-4-13-I the First Class of Treatment was IDR. 3.716.554; Second Class of Treatment was IDR 2.930.222; Third Class of treatment was IDR 3.009.750. In C-4-13-II, the First Class of Treatment was IDR. 7.680.392; Third Class of treatment was IDR 6.351.268, and in C-4-13-III, the First Class of Treatment was IDR. 10.179.575; Third Class of treatment was IDR 10.031.690. Accommodation cost the highest component of real cost. The irregular cycle pattern had the higher mean real cost than the regular of chemotherapy cycles